Implementasi Penegakan Hukum Pidana Oleh Kepolisian Terhadap Pelaku Pelanggaran Lalu Lintas Di Kota PadangImplementasi Penegakan Hukum Pidana Oleh Kepolisian Terhadap Pelaku Pelanggaran Lalu Lintas Di Kota Padang - Ilham Wardhana Putra (CV. ITTC INDONESIA, 2025)
Road traffic plays a crucial role in supporting the smooth running of development and public mobility. However, to achieve effectiveness in the transportation system, proper law enforcement is needed. This study aims to analyze the implementation of criminal law enforcement by the police against traffic violations in Padang City. The study uses a qualitative approach with a descriptive method. Data were collected through interviews with the police, drivers, and the public, as well as field observations. The results show that the police have made efforts to enforce the law by imposing sanctions on traffic violations, but there are obstacles in its implementation, such as the lack of public awareness of traffic regulations, inadequate facilities and infrastructure, and weak supervision. Nevertheless, the effectiveness of law enforcement can be improved through increased regulation socialization, additional facilities and infrastructure, and strengthened coordination between related agencies. Consistent and continuous law enforcement will strengthen public awareness in maintaining order and safety on the road.